Composition and fracturing fluid containing same
By using a composition of organopolysiloxane, emulsifier and accelerator, the pH fracturing fluid is adjusted, and the problem of insufficient wettability improvement ability of reservoirs is solved, thereby achieving a significant reduction in the permeability of water and gas phase. The slightly reduced permeability meets the needs of water-controlled fracturing technology.
Patent Information
- Application Number
- CN202310725683.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-19
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-06-19
AI Technical Summary
In the existing water-controlled fracturing technology, the wettability improvement capacity of reservoir rocks is limited, which makes it difficult for fluids to enter the reservoir and affects the gas well production capacity.
Using a composition including organopolysiloxane, emulsifier, co-emulsifier and water, the reservoir wetting and fluid injection capacity is improved by adjusting the fracturing fluid at a pH of 7.5 to 10.
A significant reduction in water-phase permeability (60% to 75%) and a slight decrease in gas-phase permeability (2.7% to 7.8%) was achieved, ensuring the effect of blocking water and not blocking gas, and it is suitable for water-controlled fracturing applications.
Smart Images

Figure CN119161865A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oilfield chemistry, and in particular relates to a composition and a fracturing fluid containing the composition. Background Art
[0002] Tight low-permeability water-bearing gas reservoirs need to be hydraulically fractured to achieve commercial production capacity, but water-controlled fracturing and increasing gas well production in water-bearing gas reservoirs have always been technical problems that plague oil and gas field development. For gas reservoirs with bottom water layers, artificial fractures may communicate with the bottom water layer, causing the water content of the gas well to increase; for gas reservoirs with gas and water in the same layer, formation water may block tiny rock pores, causing a water lock effect and affecting gas well production capacity. There are several main methods to solve the practical problems of water-controlled fracturing: first, by controlling the fracturing construction parameters, controlling the geometric size of the fractures, avoiding the aquifer, and achieving water-controlled fracturing; second, by reducing the flow capacity of formation water in the fractures, the purpose of water-controlled fracturing is achieved; third, by forming an artificial barrier layer, controlling the bottom water cone advance, and controlling the water production of oil and gas wells; fourth, by adjusting the wettability of reservoir rocks, reducing the water phase permeability, and controlling the water production of oil and gas wells. Among them, adjusting the wettability of reservoir rocks, reducing the water phase permeability, and controlling the water production of oil and gas wells is a more widely used method.
[0003] Although water-controlled fracturing technology has been studied in various aspects such as fracturing design, fracturing fluid, proppant, and temporary plugging agent at home and abroad, water-controlled fracturing still faces huge challenges due to the complexity of reservoir rocks and fluids. Once formation water continues to flow into artificial fractures, there is a high probability that the gas production of the gas well will drop significantly. Therefore, reducing the flow capacity of formation water in reservoir rocks without changing the flow capacity of natural gas is the key to water-controlled fracturing technology. Existing technologies mainly reduce the ability of formation water to flow into fractures and wellbores by changing the wettability of reservoir rocks, but there are problems such as difficulty in fluid entering the reservoir and limited ability to change the wettability of the reservoir. Summary of the invention
[0004] In view of the above problems, the object of the present invention is to provide a fracturing fluid which has strong reservoir wettability improvement capability and is easy to inject into the reservoir.
[0005] To achieve the above object, the first aspect of the present invention provides a composition comprising an organopolysiloxane, an emulsifier, a co-emulsifier and water.
[0006] According to a specific embodiment of the present invention, taking the mass of the composition as 100%, the composition includes 10wt% to 30wt% of the organopolysiloxane, 20wt% to 40wt% of the emulsifier, 5wt% to 15wt% of the co-emulsifier and the balance of water.
[0007] According to a specific embodiment of the present invention, the structural schematic diagram of the organopolysiloxane is shown in Formula I:
[0008]
[0009] Wherein, R is phenyl, C2 to C 12 One of an alkyl group and a trifluoropropyl group;
[0010] a, b and c are the number of structural units; a, b, c are integers from 4 to 80, 1 to 10 and 2 to 20, respectively;
[0011] The relative molecular mass of the organopolysiloxane is 700 to 10000;
[0012] Preferably, in the formula I, R is phenyl; and / or
[0013] The relative molecular weight of the organopolysiloxane is 700 to 8700; and / or
[0014] a, b and c are integers from 10 to 60, 2 to 8 and 5 to 18 respectively;
[0015] Preferably, a, b and c are integers of 20 to 60, 5 to 8 and 10 to 18 respectively.
[0016] Formula I only reflects the types of structural units in the organopolysiloxane and the quantitative relationship of each structural unit, and does not represent the specific structure of the organopolysiloxane.
[0017] According to a specific embodiment of the present invention, the emulsifier is a mixture of a nonionic surfactant and an anionic surfactant; and / or
[0018] The auxiliary emulsifier is an alcohol compound and / or an alcohol ether compound.
[0019] According to a specific embodiment of the present invention, the nonionic surfactant is a nonionic silicone surfactant and / or a sorbitan fatty acid ester; and / or
[0020] The anionic surfactant is selected from at least one of alkylbenzene sulfonate, α-olefin sulfonate and alkyl sulfate; and / or
[0021] The alcohol compound is at least one of n-propanol, isopropanol, n-butanol, isobutanol, ethylene glycol, propylene glycol and glycerol; and / or
[0022] The alcohol ether compound is a C4 to C6 alcohol ether.
[0023] According to a specific embodiment of the present invention, the general structural formula of the nonionic silicone surfactant is as shown in Formula II:
[0024]
[0025] Wherein, x, y and z are the number of structural units, and x, y and z are integers from 1 to 10, 2 to 10 and 2 to 10, respectively;
[0026] Preferably, in the formula II, x, y and z are integers of 1 to 6, 5 to 10 and 5 to 10 respectively;
[0027] Preferably, x, y and z are integers of 1 to 5, 5 to 10 and 5 to 10 respectively.
[0028] Generally, commercially available nonionic silicone surfactants with a structural formula within the scope of the general structural formula II can be used in the present invention.
[0029] According to a specific embodiment of the present invention, the sorbitan fatty acid ester is selected from at least one of sorbitan monolaurate (SPAN-20), sorbitan monopalmitate (SPAN-40), sorbitan monostearate (SPAN-60) and sorbitan monooleate (SPAN-80); and / or
[0030] The anionic surfactant is selected from at least one of sodium dodecylbenzene sulfonate, sodium α-olefin sulfonate and sodium dodecyl sulfate; and / or
[0031] The alcohol ether compound is diethylene glycol ether and / or triethylene glycol ether.
[0032] The sodium α-olefin sulfonate used in the present invention is C 12 To C 18 A mixture of sodium alpha-olefin sulfonates.
[0033] According to a specific embodiment of the present invention, in the emulsifier, the mass ratio of the nonionic surfactant to the anionic surfactant is 6:4 to 4:6.
[0034] According to a specific embodiment of the present invention, the composition is prepared by the following steps:
[0035] 1) mixing the organopolysiloxane, an emulsifier and a co-emulsifier to obtain an emulsifier-co-emulsifier dispersion system;
[0036] 2) mixing water and the emulsifier-co-emulsifier dispersion system to obtain the composition.
[0037] According to a specific embodiment of the present invention, in step 1), mixing is performed by stirring; and / or
[0038] In step 2), water is added to the emulsifier-co-emulsifier dispersion system under stirring; and / or
[0039] After the water is added, stirring is performed to obtain the composition;
[0040] Preferably, the stirring speed in step 1) and step 2) is independently 50 r / min to 100 r / min; and / or
[0041] The duration of stirring in step 1), the duration of adding water in step 2), and the duration of stirring after adding water in step 2) are independently 20 min to 40 min.
[0042] A second aspect of the present invention provides a fracturing fluid comprising a composition and water;
[0043] The composition is the composition described in the first aspect of the present invention.
[0044] According to a specific embodiment of the present invention, taking the mass of the fracturing fluid as 100%, the fracturing fluid comprises 0.2 wt % to 1.0 wt % of the composition and the balance being water.
[0045] According to a specific embodiment of the present invention, in practical application, the pH of the fracturing fluid is first adjusted to 7.5 to 10 before use;
[0046] Preferably, the pH is adjusted using a pH adjuster;
[0047] Preferably, the pH regulator is selected from hydroxides, carbonates, bicarbonates, ammonia and amine compounds;
[0048] Further preferably, the pH adjuster is at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, ammonia water, methylamine, trimethylamine, ethylamine and ethylenediamine.
[0049] Use of the composition according to the first aspect of the present invention or the fracturing fluid according to the second aspect of the present invention in water controlled fracturing.
[0050] The third aspect of the present invention provides a method for preparing the organopolysiloxane:
[0051] A. mixing a first siloxane monomer, a second siloxane monomer, a third siloxane monomer and a fourth siloxane monomer to obtain a monomer mixture;
[0052] B. Mixing the catalyst and the monomer mixture, reacting, and purifying to obtain the organopolysiloxane.
[0053] According to a specific embodiment of the present invention, the mass of the monomer mixture is calculated as 100%, and the monomer mixture includes 38wt% to 74wt% of the first siloxane monomer, 11.5wt% to 31wt% of the second siloxane monomer, 13.5wt% to 35.5wt% of the third siloxane monomer and 0.4wt% to 7wt% of the fourth siloxane monomer; and / or
[0054] The mass of the monomer mixture is taken as 100%, and the amount of the catalyst is 1.3 wt % to 1.71 wt %.
[0055] According to a specific embodiment of the present invention, the first siloxane monomer is octamethylcyclotetrasiloxane; and / or
[0056] The second siloxane monomer is 1,3,5,7-tetramethylcyclotetrasiloxane; and / or
[0057] The third siloxane monomer is at least one selected from 1,3,5,7-tetramethyltetraphenylcyclotetrasiloxane, 1,3,5,7-tetramethyltetra(dodecyl)cyclotetrasiloxane, 1,3,5,7-tetramethyltetraethylcyclotetrasiloxane and 1,3,5-trifluoropropylmethylcyclotrisiloxane; and / or
[0058] The fourth siloxane monomer is hexamethyldisiloxane; and / or
[0059] The catalyst is a strong acid and / or a cation exchange resin;
[0060] Preferably, the catalyst is concentrated sulfuric acid.
[0061] According to a specific embodiment of the present invention, the monomer mixture is first deoxygenated, and then the step B is performed;
[0062] Preferably, an inert gas (such as nitrogen) is introduced into the monomer mixed liquid to perform the deoxygenation.
[0063] According to a specific embodiment of the present invention, the catalyst is added while stirring; and / or
[0064] In step B, the reaction product obtained after the reaction is cooled, the pH is adjusted to neutral, and then the purification is performed; preferably, the cooling is to room temperature; and / or the pH is adjusted with a base (such as sodium carbonate); and / or
[0065] The purification was performed as follows:
[0066] The reaction product after the pH is adjusted to neutral is filtered, and the filtrate is collected and subjected to reduced pressure distillation to obtain the purified organopolysiloxane;
[0067] Preferably, the conditions for the reduced pressure distillation are reduced pressure distillation at -0.09 MPa to -0.095 MPa and 40° C. to 50° C. for 30 min to 60 min.
[0068] According to a specific embodiment of the present invention, the reaction condition is 60°C to 80°C for 4h to 12h. Beneficial effects of the present invention:
[0069] In view of the problems in the prior art that water-control fracturing agents are difficult to enter the reservoir and have limited ability to change the wettability of the reservoir, the present invention provides a composition and a fracturing fluid containing the same. The composition provided by the present invention includes an organopolysiloxane, an emulsifier, an emulsifier aid and water; the fracturing fluid provided by the present invention is obtained by further compounding the composition with water. The fracturing fluid is an emulsion. In practical applications, the pH of the fracturing fluid is first adjusted to 7.5 to 10 before use. The average particle size of the emulsion droplets of the fracturing fluid before and after pH adjustment is 90nm to 158nm and 81nm to 169nm, respectively. After pH adjustment, the particle size of the emulsion droplets of the fracturing fluid is still very small and easy to inject into the reservoir; the surface tension of the fracturing fluid before and after pH adjustment is 25.3mN·m -1 Up to 28.8mN·m -1 、20.4mN·m -1 Up to 26.4mN·m -1 After adjusting the pH, the fracturing fluid still has a strong ability to improve reservoir wettability; before adjusting the pH, the fracturing fluid can be stably stored for more than 30 days, which is convenient for storage; after adjusting the pH, the stable storage time of the fracturing fluid is still 4 to 6 days, the storage time will not be too short, and it is convenient to operate in actual use; the water control experiment measured that the fracturing fluid after adjusting the pH makes the water phase permeability change from K W,1 From 4.8219 to 5.9273mD down to K W,2 From 1.2983 to 2.1627 mD, the water permeability decreased by 60% to 75%; the gas permeability increased from K g,1 From 19.1017 to 28.4622mD down to K g,2 The pH value of the fracturing fluid is 18.5743 to 26.3458 mD, the gas phase permeability decreases by 2.7% to 7.8%, the water phase permeability decreases by a large margin, while the gas phase permeability decreases by a small margin, achieving the effect of blocking water without blocking gas; in addition, the dimensionless fluid resistance ratio NFRR of the fracturing fluid after pH adjustment is 2.3465 to 3.7313, which is significantly greater than 1, proving that the fracturing fluid after pH adjustment selectively reduces the water phase permeability without affecting the gas phase permeability, can meet the demand of water control fracturing technology for fracturing fluid, and is suitable for promotion and use in water control fracturing. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 The hydrogen nuclear magnetic resonance spectrum of the organopolysiloxane prepared in Example 2;
[0071] Figure 2 The hydrogen nuclear magnetic resonance spectrum of the organopolysiloxane prepared in Example 4;
[0072] Figure 3 This is the hydrogen nuclear magnetic resonance spectrum of the organopolysiloxane prepared in Example 6;
[0073] Figure 4 The infrared spectrum of the organopolysiloxane prepared in Example 2;
[0074] Figure 5 The infrared spectrum of the organopolysiloxane prepared in Example 4;
[0075] Figure 6 This is the infrared spectrum of the organopolysiloxane prepared in Example 6. DETAILED DESCRIPTION
[0076] The present invention will be further described below in conjunction with examples, but the examples of the present invention are only exemplary descriptions, and the implementation methods do not constitute limitations of the present invention under any circumstances.
[0077] Preparation of organopolysiloxane
[0078] Example 1
[0079] A. 49.3 kg of octamethylcyclotetrasiloxane, 20 kg of 1,3,5,7-tetramethylcyclotetrasiloxane, 22.6 kg of 1,3,5,7-tetramethyltetraphenylcyclotetrasiloxane and 6.8 kg of hexamethyldisiloxane were mixed to obtain a monomer solution;
[0080] B. Nitrogen was passed through the monomer solution for 30 minutes to remove oxygen, and then 1.5 kg of concentrated sulfuric acid was added dropwise while stirring, and the mixture was heated to 65°C for reaction for 8 hours; after the reaction, the mixture was cooled to room temperature (25°C), and sodium carbonate was slowly added to adjust the pH of the reaction product to neutral, the reaction product was filtered, and the filtrate was collected and distilled under reduced pressure at -0.09 MPa and 40°C for 30 minutes to obtain an organopolysiloxane as shown in the structural diagram of Formula I-1:
[0081]
[0082] Its relative molecular mass is 714, and the corresponding organopolysiloxane structural diagram, in Formula Ⅰ, R is phenyl, and a, b, and c are 4, 1, and 2 respectively.
[0083] Example 2
[0084] A. 69.5 kg of octamethylcyclotetrasiloxane, 14 kg of 1,3,5,7-tetramethylcyclotetrasiloxane, 15.9 kg of 1,3,5,7-tetramethyltetraphenylcyclotetrasiloxane and 0.48 kg of hexamethyldisiloxane were mixed to obtain a monomer solution;
[0085] B. Nitrogen was passed through the monomer solution for 30 minutes to remove oxygen, and then 1.3 kg of concentrated sulfuric acid was added dropwise while stirring, and the mixture was heated to 60°C for reaction for 10 hours; after the reaction, the mixture was cooled to room temperature (25°C), and sodium carbonate was slowly added to adjust the pH of the reaction product to neutral, the reaction product was filtered, and the filtrate was collected and distilled under reduced pressure at -0.09 MPa and 40°C for 30 minutes to obtain an organopolysiloxane as shown in the structural diagram of Formula I-2:
[0086]
[0087] Its relative molecular mass is 8642, and the corresponding organopolysiloxane structural diagram, in Formula Ⅰ, R is phenyl, and a, b, and c are 80, 10, and 20 respectively.
[0088] Example 3
[0089] A. 73.6 kg of octamethylcyclotetrasiloxane, 11.9 kg of 1,3,5,7-tetramethylcyclotetrasiloxane, 13.5 kg of 1,3,5,7-tetramethyltetraphenylcyclotetrasiloxane and 0.8 kg of hexamethyldisiloxane were mixed uniformly to obtain a monomer solution;
[0090] B. Nitrogen was passed through the monomer solution for 30 minutes to remove oxygen, and then 1.7 kg of concentrated sulfuric acid was added dropwise while stirring, and the mixture was heated to 70°C for reaction for 4 hours; after the reaction, the mixture was cooled to room temperature (25°C), and sodium carbonate was slowly added to adjust the pH of the reaction product to neutral, the reaction product was filtered, and the filtrate was collected and distilled under reduced pressure at -0.090 MPa and 45°C for 45 minutes to obtain an organopolysiloxane as shown in the structural diagram of Formula I-3:
[0091]
[0092] Its relative molecular mass is 5142, and the corresponding organopolysiloxane structural diagram, in Formula Ⅰ, R is phenyl, and a, b, and c are 50, 5, and 10 respectively.
[0093] Example 4
[0094] A. 43.2 kg of octamethylcyclotetrasiloxane, 21 kg of 1,3,5,7-tetramethylcyclotetrasiloxane, 35.4 kg of 1,3,5,7-tetramethyltetra(dodecyl)cyclotetrasiloxane and 0.8 kg of hexamethyldisiloxane were mixed to obtain a monomer solution;
[0095] B. Nitrogen was passed through the monomer solution for 30 minutes to remove oxygen, and then 1.6 kg of concentrated sulfuric acid was added dropwise while stirring, and the mixture was heated to 70°C for reaction for 6 hours; after the reaction, the mixture was cooled to room temperature (25°C), and sodium carbonate was slowly added to adjust the pH of the reaction product to neutral, the reaction product was filtered, and the filtrate was collected and distilled under reduced pressure at -0.095 MPa and 45°C for 45 minutes to obtain an organopolysiloxane as shown in the structural diagram of Formula I-4:
[0096]
[0097] Its relative molecular mass is 5286, and the R in the corresponding organopolysiloxane structural diagram Formula I is -C 12 H 25 , a, b, c are 30, 8, 18 respectively.
[0098] Example 5
[0099] A. 71 kg of octamethylcyclotetrasiloxane, 14.4 kg of 1,3,5,7-tetramethylcyclotetrasiloxane, 14 kg of 1,3,5,7-tetramethyltetraethylcyclotetrasiloxane and 0.65 kg of hexamethyldisiloxane were mixed to obtain a monomer solution;
[0100] B. Nitrogen was passed through the monomer solution for 30 minutes to remove oxygen, and then 1.5 kg of concentrated sulfuric acid was added dropwise while stirring, and the mixture was heated to 60°C for reaction for 12 hours; after the reaction, the mixture was cooled to room temperature (25°C), and sodium carbonate was slowly added to adjust the pH of the reaction product to neutral, the reaction product was filtered, and the filtrate was collected and distilled under reduced pressure at -0.095 MPa and 50°C for 60 minutes to obtain an organopolysiloxane as shown in the structural diagram of Formula I-5:
[0101]
[0102] Its relative molecular mass is 6382, and the corresponding organopolysiloxane structural diagram, in Formula Ⅰ, R is -C2H5, and a, b, and c are 60, 10, and 15 respectively.
[0103] Example 6
[0104] A. 38.2 kg of octamethylcyclotetrasiloxane, 31 kg of 1,3,5,7-tetramethylcyclotetrasiloxane, 30 kg of 1,3,5-trifluoropropylmethylcyclotrisiloxane and 1 kg of hexamethyldisiloxane were mixed to obtain a monomer solution;
[0105] B. Nitrogen was passed through the monomer solution for 30 minutes to remove oxygen, and then 1.6 kg of concentrated sulfuric acid was added dropwise while stirring, and the mixture was heated to 80°C for reaction for 4 hours; after the reaction, the mixture was cooled to room temperature (25°C), and sodium carbonate was slowly added to adjust the pH of the reaction product to neutral. The reaction product was filtered, and the filtrate was collected and distilled under reduced pressure at -0.095 MPa and 50°C for 60 minutes to obtain an organopolysiloxane as shown in the structural diagram of Formula I-6:
[0106]
[0107] Its relative molecular mass is 4402, and the corresponding organopolysiloxane structural diagram, in Formula Ⅰ, R is -C2H4CF3, and a, b, and c are 20, 10, and 20 respectively.
[0108] Example 7
[0109] A. 53.3 kg of octamethylcyclotetrasiloxane, 21.6 kg of 1,3,5,7-tetramethylcyclotetrasiloxane, 24.5 kg of 1,3,5,7-tetramethyltetraphenylcyclotetrasiloxane and 0.73 kg of hexamethyldisiloxane were mixed to obtain a monomer solution;
[0110] B. Nitrogen was passed through the monomer solution for 30 minutes to remove oxygen, and then 1.5 kg of concentrated sulfuric acid was added dropwise while stirring, and the mixture was heated to 70°C for reaction for 6 hours; after the reaction, the mixture was cooled to room temperature (25°C), and sodium carbonate was slowly added to adjust the pH of the reaction product to neutral, the reaction product was filtered, and the filtrate was collected and distilled under reduced pressure at -0.095 MPa and 50°C for 60 minutes to obtain an organopolysiloxane as shown in the structural schematic diagram of Formula I-7:
[0111]
[0112] Its relative molecular mass is 5682, and the corresponding organopolysiloxane structural diagram, in Formula Ⅰ, R is phenyl, and a, b, and c are 40, 10, and 20 respectively.
[0113] Structural Characterization of Organopolysiloxane
[0114] The chemical structures of the organopolysiloxanes prepared in Examples 1 to 7 were determined using a Brune Advance III nuclear magnetic resonance spectrometer and a Thermo Scientific Nicolet iS5 infrared spectrometer. Here, the nuclear magnetic resonance hydrogen spectra and infrared spectra of the organopolysiloxanes prepared in Examples 2, 4 and 6 were taken as examples for specific analysis.
[0115] Figure 1This is the hydrogen nuclear magnetic resonance spectrum of the organopolysiloxane prepared in Example 2. The chemical shifts of different protons in the spectrum are assigned as follows: 7.54, 7.33, 7.23 (≡Si-C6H5), 3.46 (≡Si-H), 0.39 (=Si(Ph)-CH3), 0.09 (≡Si-CH3). Figure 4 This is the infrared spectrum of the organopolysiloxane prepared in Example 2. The absorption peaks on the spectrum are: 606 cm -1 It is the absorption peak of CH bending vibration on -CH3, 902cm -1 The Si-C bending vibration absorption peak of -Si-CH3 is 1047cm -1 is the stretching vibration absorption peak of -Si-O-Si-, 1292cm -1 -Si-C stretching vibration absorption peak of -Si-CH3, 1536cm -1 The CC stretching vibration absorption peak on the benzene ring is 2163 cm -1 -Si-H stretching vibration absorption peak, 2920cm -1 is the stretching vibration absorption peak of -CH3, 3017cm -1 It is the absorption peak of CH stretching vibration on the benzene ring.
[0116] Combination Figure 1 and Figure 4 It is proved that the structural schematic diagram of the organopolysiloxane prepared in Example 2 is indeed as shown in Formula Ⅰ-2.
[0117] Figure 2 This is the hydrogen nuclear magnetic resonance spectrum of the organopolysiloxane prepared in Example 4. The chemical shifts of different protons in the spectrum are assigned as follows: 3.3 (≡Si-H), 1.49, 1.27, 0.87 (≡Si-C 12 H 25 ), 0.14, 0.04 (≡Si-CH3). Figure 5 This is the infrared spectrum of the organopolysiloxane prepared in Example 4. The absorption peaks on the spectrum are: 609cm -1 It is the absorption peak of CH bending vibration on -CH3, 898cm -1 The Si-C bending vibration absorption peak of -Si-CH3 is 1081cm -1 The stretching vibration absorption peak of -Si-O-Si- is 1268cm -1 -Si-C stretching vibration absorption peak of -Si-CH3, 1434cm -1 -CH2 symmetric bending vibration absorption peak, 2161cm -1 -Si-H stretching vibration absorption peak, 2920cm -1 It is the stretching vibration absorption peak of -CH3.
[0118] Combination Figure 2 and Figure 5 It is proved that the structural schematic diagram of the organopolysiloxane prepared in Example 4 is indeed as shown in Formula Ⅰ-4.
[0119] Figure 3 This is the hydrogen nuclear magnetic resonance spectrum of the organopolysiloxane prepared in Example 6. The chemical shifts of different protons in the spectrum are assigned as follows: 3.3 (≡Si-H), 2.08, 1.03 (≡Si-CH2-CH2-CF3), 0.14, 0.04 (≡Si-CH3). Figure 6 This is the infrared spectrum of the organopolysiloxane prepared in Example 6. The absorption peaks on the spectrum are: 597 cm -1 It is the absorption peak of CH bending vibration on -CH3, 864-905cm -1 The Si-C bending vibration absorption peak of -Si-CH3 is 1022cm -1 The stretching vibration absorption peak of -Si-O-Si- is 1286-1328cm -1 CF stretching vibration absorption peak, 1404cm -1 -CH2 symmetric bending vibration absorption peak, 2155cm -1 -Si-H stretching vibration absorption peak, 2927cm -1 It is the stretching vibration absorption peak of -CH3.
[0120] Combination Figure 3 and Figure 6 It is proved that the structural schematic diagram of the organopolysiloxane prepared in Example 6 is indeed as shown in Formula Ⅰ-6.
[0121] In addition, in the hydrogen NMR spectrum of the organopolysiloxane prepared in Example 1, chemical shifts corresponding to the protons of ≡Si-C6H5, ≡Si-H, =Si(Ph)-CH3 and ≡Si-CH3 can be observed; in the hydrogen NMR spectrum of the organopolysiloxane prepared in Example 3, chemical shifts corresponding to the protons of ≡Si-C6H5, ≡Si-H, =Si(Ph)-CH3 and ≡Si-CH3 can be observed; in the hydrogen NMR spectrum of the organopolysiloxane prepared in Example 5, chemical shifts of the protons of ≡Si-H, ≡Si-C2H5 and ≡Si-CH3 can be observed; in the hydrogen NMR spectrum of the organopolysiloxane prepared in Example 7, chemical shifts corresponding to the protons of ≡Si-C6H5, ≡Si-H, =Si(Ph)-CH3 and ≡Si-CH3 can be observed. In the infrared spectra of the organopolysiloxanes prepared in Example 1, Example 3, and Example 7, the CH bending vibration absorption peak on -CH3, the Si-C bending vibration absorption peak of -Si-CH3, the stretching vibration absorption peak of -Si-O-Si-, the Si-C stretching vibration absorption peak of -Si-CH3, the CC stretching vibration absorption peak on the benzene ring, the stretching vibration absorption peak of -Si-H, the stretching vibration absorption peak of -CH3, and the CH stretching vibration absorption peak on the benzene ring can be observed; in the infrared spectrum of the organopolysiloxane prepared in Example 5, the CH bending vibration absorption peak on -CH3, the Si-C bending vibration absorption peak of -Si-CH3, the stretching vibration absorption peak of -Si-O-Si-, the Si-C stretching vibration absorption peak of -Si-CH3, the symmetric bending vibration absorption peak of -CH2, the stretching vibration absorption peak of -Si-H, and the stretching vibration absorption peak of -CH3 can be observed. The structural schematic diagrams of the organopolysiloxanes prepared in Examples 1, 3, 5, and 7 are shown in Formulas Ⅰ-1, Ⅰ-3, Ⅰ-5, and Ⅰ-7, respectively.
[0122] Preparation of composition
[0123] The sodium α-olefin sulfonate used in Examples 9 and 13 is C 12 To C 18 A mixture of sodium α-olefin sulfonates was purchased from Jinan Huifengda Chemical Co., Ltd. with a CAS number of 68439-57-6.
[0124] Example 8
[0125] The structural formula of the nonionic silicone surfactant used in this embodiment is shown in Formula II-1:
[0126]
[0127] In the general structural formula II of the nonionic silicone surfactant, x, y, and z are 1, 2, and 2 respectively.
[0128] 1) Weigh 10 g of a nonionic silicone surfactant of formula II-1, 10 g of sodium lauryl sulfate and 5 g of diethylene glycol ether and add them to 30 g of the organopolysiloxane of formula I-1 prepared in Example 1, and stir at a speed of 50 r / min for 30 min to obtain an emulsifier-co-emulsifier dispersion system;
[0129] 2) while stirring the emulsifier-co-emulsifier dispersion system at a speed of 50 r / min, 45 g of water is slowly added thereto, and the time of adding water is controlled to be 30 min; after the water is added, stirring is continued at a speed of 50 r / min for 30 min at room temperature (25° C.) to obtain a composition, which is a microemulsion for water-controlled fracturing.
[0130] Example 9
[0131] The structural formula of the nonionic silicone surfactant used in this embodiment is shown in Formula II-2:
[0132]
[0133] In the general structural formula II of the nonionic silicone surfactant, x, y and z are all 10.
[0134] 1) Weigh 24 g of a nonionic silicone surfactant of formula II-2, 16 g of sodium α-olefin sulfonate and 15 g of triethylene glycol ether and add them to 10 g of the organopolysiloxane of formula I-2 prepared in Example 2, and stir at a speed of 60 r / min for 30 min to obtain an emulsifier-co-emulsifier dispersion system;
[0135] 2) while stirring the emulsifier-co-emulsifier dispersion system at a speed of 60 r / min, 35 g of water is slowly added thereto, and the time of adding water is controlled within 30 min; after the water is added, stirring is continued at a speed of 60 r / min for 30 min at room temperature (25° C.) to obtain a composition, which is a microemulsion for water-controlled fracturing.
[0136] Example 10
[0137] The structural formula of the nonionic silicone surfactant used in this embodiment is shown in Formula II-3:
[0138]
[0139] In the general structural formula II of the nonionic silicone surfactant, x, y, and z are 6, 5, and 5 respectively.
[0140] 1) 12 g of a nonionic silicone surfactant of formula II-3, 18 g of sodium dodecylbenzene sulfonate, 3 g of n-propanol and 7 g of n-butanol were added to 20 g of the organopolysiloxane of formula I-3 prepared in Example 3, and stirred at a speed of 70 r / min for 30 min to obtain an emulsifier-co-emulsifier dispersion system;
[0141] 2) while stirring the emulsifier-co-emulsifier dispersion system at a speed of 70 r / min, 40 g of water is slowly added thereto, and the time of adding water is controlled within 30 min; after the water is added, stirring is continued at a speed of 70 r / min for 30 min at room temperature (25° C.) to obtain a composition, which is a microemulsion for water control fracturing.
[0142] Embodiment 11
[0143] The structural formula of the nonionic silicone surfactant used in this embodiment is shown in Formula II-4:
[0144]
[0145] In the general structural formula II of the nonionic silicone surfactant, x, y and z are 2, 10 and 10 respectively.
[0146] 1) 12.5 g of a nonionic silicone surfactant of formula II-4, 12.5 g of sodium dodecylbenzene sulfonate, 3.6 g of isobutyl alcohol and 2.4 g of ethylene glycol were added to 18 g of the organopolysiloxane of formula I-4 prepared in Example 4, and stirred at a speed of 80 r / min for 30 min to obtain an emulsifier-co-emulsifier dispersion system;
[0147] 2) while stirring the emulsifier-co-emulsifier dispersion system at a speed of 80 r / min, 51 g of water was slowly added thereto, and the time of adding water was controlled within 30 min; after the water was added, stirring was continued at a speed of 80 r / min for 30 min at room temperature (25° C.) to obtain a composition, which is a microemulsion for water-controlled fracturing.
[0148] Example 12
[0149] 1) Weigh 11 g of sorbitan monooleate (SPAN-80), 11 g of sodium dodecylbenzene sulfonate, 2.5 g of n-propanol and 2.5 g of n-butanol and add them to 16 g of the organopolysiloxane of formula I-5 prepared in Example 5, and stir at a speed of 90 r / min for 30 min to obtain an emulsifier-co-emulsifier dispersion system;
[0150] 2) while stirring the emulsifier-co-emulsifier dispersion system at a speed of 90 r / min, 57 g of water was slowly added thereto, and the time of adding water was controlled within 30 min; after the water was added, stirring was continued at a speed of 90 r / min for 30 min at room temperature (25° C.) to obtain a composition, which is a microemulsion for water control fracturing.
[0151] Example 13
[0152] 1) 12.5 g of sorbitan monostearate (SPAN-60), 12.5 g of sodium α-olefin sulfonate, 4 g of n-butanol and 4 g of propylene glycol were added to 20 g of the organopolysiloxane of formula I-6 prepared in Example 6, and stirred at a speed of 100 r / min for 30 min to obtain an emulsifier-co-emulsifier dispersion system;
[0153] 2) while stirring the emulsifier-co-emulsifier dispersion system at a speed of 100 r / min, 47 g of water is slowly added thereto, and the time of adding water is controlled to be 30 min; after the water is added, stirring is continued at a speed of 100 r / min for 30 min at room temperature (25°C) to obtain a composition, which is a microemulsion for water control fracturing.
[0154] Embodiment 14
[0155] 1) Weigh 20 g of sorbitan monooleate (SPAN-80), 20 g of sodium dodecylbenzene sulfonate, 5 g of isopropyl alcohol and 5 g of diethylene glycol ether and add them to 25 g of the organopolysiloxane of formula I-7 prepared in Example 7, and stir at a speed of 100 r / min for 30 min to obtain an emulsifier-co-emulsifier dispersion system;
[0156] 2) while stirring the emulsifier-co-emulsifier dispersion system at a speed of 100 r / min, slowly add 25 g of water thereto, and the time of adding water is controlled within 30 min; after the water is added, continue to stir at a speed of 100 r / min for 30 min at room temperature (25° C.) to obtain a composition, which is a microemulsion for water-controlled fracturing.
[0157] Embodiment 15
[0158] 1) 21.82 g of sorbitan monopalmitate (SPAN-40), 18.18 g of sodium dodecylbenzene sulfonate, 3.33 g of isopropyl alcohol and 6.67 g of triethylene glycol ether were added to 25 g of the organopolysiloxane of formula I-7 prepared in Example 7, and stirred at a speed of 100 r / min for 30 min to obtain an emulsifier-co-emulsifier dispersion system;
[0159] 2) while stirring the emulsifier-co-emulsifier dispersion system at a speed of 70 r / min, slowly add 25 g of water thereto, and the time of adding water is controlled to be 30 min; after the water is added, continue to stir at a speed of 70 r / min for 30 min at room temperature (25° C.) to obtain a composition, which is a microemulsion for water-controlled fracturing.
[0160] Example 16
[0161] 1) 16.36 g of sorbitan monolaurate (SPAN-20), 13.64 g of sodium lauryl sulfate, 2.67 g of isopropyl alcohol and 5.33 g of glycerol were added to 21 g of the organopolysiloxane of formula I-7 prepared in Example 7, and stirred at a speed of 100 r / min for 30 min to obtain an emulsifier-co-emulsifier dispersion system;
[0162] 2) while stirring the emulsifier-co-emulsifier dispersion system at a speed of 80 r / min, 41 g of water was slowly added thereto, and the time of adding water was controlled within 30 min; after the water was added, stirring was continued at a speed of 80 r / min for 30 min at room temperature (25° C.) to obtain a composition, which is a microemulsion for water-controlled fracturing.
[0163] Preparation of fracturing fluid
[0164] Embodiment 17
[0165] At room temperature (25°C), 0.3 g of the composition prepared in Example 8 was added to 99.7 g of water at a speed of 100 r / min and mixed evenly to obtain a fracturing fluid, which was an emulsion; sodium hydroxide was then added to the obtained fracturing fluid to adjust the pH to 9.2 for use.
[0166] Embodiment 18
[0167] At room temperature (25°C), 0.3 g of the composition prepared in Example 9 was added to 99.7 g of water at a speed of 100 r / min and mixed evenly to obtain a fracturing fluid, which was an emulsion; sodium hydroxide was then added to the obtained fracturing fluid to adjust the pH to 9.2 for use.
[0168] Embodiment 19
[0169] At room temperature (25°C), 0.3 g of the composition prepared in Example 10 was added to 99.7 g of water at a speed of 100 r / min and mixed evenly to obtain a fracturing fluid, which was an emulsion; sodium hydroxide was added to the obtained fracturing fluid to adjust the pH to 9.2 for use.
[0170] Embodiment 20
[0171] At room temperature (25°C), 0.3 g of the composition prepared in Example 11 was added to 99.7 g of water at a speed of 90 r / min and mixed evenly to obtain a fracturing fluid, which was an emulsion; potassium hydroxide was added to the obtained fracturing fluid to adjust the pH to 9.3 for use.
[0172] Embodiment 21
[0173] At room temperature (25°C), 0.3 g of the composition prepared in Example 12 was added to 99.7 g of water at a speed of 90 r / min and mixed evenly to obtain a fracturing fluid, which was an emulsion; potassium hydroxide was added to the obtained fracturing fluid to adjust the pH to 9.3 for use.
[0174] Embodiment 22
[0175] At room temperature (25°C), 0.3 g of the composition prepared in Example 13 was added to 99.7 g of water at a speed of 50 r / min and mixed evenly to obtain a fracturing fluid, which is an emulsion; ammonia water was then added to the obtained fracturing fluid to adjust the pH to 9.8 for use.
[0176] Embodiment 23
[0177] At room temperature (25°C), 0.3 g of the composition prepared in Example 14 was added to 99.7 g of water at a speed of 80 r / min and mixed evenly to obtain a fracturing fluid, which was an emulsion; trimethylamine was then added to the obtained fracturing fluid to adjust the pH to 10 for use.
[0178] Embodiment 24
[0179] At room temperature (25°C), 0.3 g of the composition prepared in Example 15 was added to 99.7 g of water at a speed of 80 r / min and mixed evenly to obtain a fracturing fluid, which was an emulsion; trimethylamine was added to the obtained fracturing fluid to adjust the pH to 10 for use.
[0180] Embodiment 25
[0181] At room temperature (25°C), 0.3 g of the composition prepared in Example 16 was added to 99.7 g of water at a speed of 70 r / min and mixed evenly to obtain a fracturing fluid, which is an emulsion; ethylenediamine was then added to the obtained fracturing fluid to adjust the pH to 9.5 for use.
[0182] Experimental evaluation
[0183] 1. Determination of fracturing fluid performance parameters
[0184] The emulsion droplet size, surface tension and stable storage time of the fracturing fluids prepared in Examples 17 to 25 were measured at room temperature (25° C.) before and after pH adjustment. The specific method is as follows:
[0185] i. Determination of the particle size of the emulsion droplets of the fracturing fluid: The particle sizes of the emulsion droplets of the fracturing fluids prepared in Examples 17 to 25 before and after pH adjustment were measured using a Malvin MasterSizer 3000 laser particle size analyzer.
[0186] ii. Determination of surface tension of fracturing fluid: The surface tension of the fracturing fluids prepared in Examples 17 to 25 before and after pH adjustment was measured using a JYW-200 surface tension meter.
[0187] ⅲ Determination of stable storage time of fracturing fluid: The fracturing fluids prepared in Examples 17 to 25 were placed for 30 days before and after pH adjustment, respectively. The state of the fracturing fluids was observed every day. The days when stratification or solid insoluble matter was observed in the fracturing fluids were the stable storage time of the fracturing fluids.
[0188] The specific results are shown in Table 1.
[0189] Table 1. Fracturing fluid performance parameters
[0190]
[0191] It can be seen from Table 1 that the fracturing fluids prepared in Examples 17 to 25 have smaller droplet size, lower interfacial tension and longer stable storage time before and after pH adjustment: the average droplet size of the fracturing fluids before and after pH adjustment is 90 nm to 158 nm and 81 nm to 169 nm, respectively. After pH adjustment, the droplet size of the fracturing fluids is still very small and is easy to inject into the reservoir; the surface tension of the fracturing fluids before and after pH adjustment is 25.3 mN·m -1 Up to 28.8mN·m -1 、20.4mN·m -1 Up to 26.4mN·m -1 After adjusting the pH, the fracturing fluid still has a strong wetting and modification ability; before adjusting the pH, the fracturing fluid can be stably stored for more than 30 days. After adjusting the pH, the stable storage time of the fracturing fluid is still 4 to 6 days. The storage time will not be too short, and it is easy to operate in actual use.
[0192] 2. Fracturing fluid water control experiment
[0193] The fracturing fluids prepared in Examples 17 to 25 after adjusting pH were used to conduct water control experiments according to the following method, and the changes in the water phase permeability and gas phase permeability of the core after the injection of the fracturing fluid were measured.
[0194] a. Take a dry core with a permeability of 5 mD, measure the size and mass of the dry core and record them; evacuate the dry core and saturate it with a 2 wt% KCl aqueous solution, wipe off the water on the surface of the core after saturation, weigh the mass of the wet core saturated with a 2 wt% KCl aqueous solution again and record it;
[0195] b. The wet core obtained in a was placed in a core flow test device, into which 10PV of 2wt% KCl aqueous solution was injected to measure the water permeability K W,1 ;
[0196] c. Inject nitrogen into the core that has completed step b until the gas flow at the core outlet is stable, and measure the gas permeability K g,1 ;
[0197] d. Inject 10PV fracturing fluid into the core that has completed step c, close the process, heat the core to 80°C, and keep the constant temperature for 1 day;
[0198] e. Inject nitrogen into the core that has completed step d until the gas flow at the core outlet is stable, and measure the gas permeability K g,2 ;
[0199] f. Inject 10PV of 2wt% KCl aqueous solution into the core after completing step e to determine the water permeability K W,2 .
[0200] The dimensionless fluid resistance ratio (NFRR) is calculated according to formula (1):
[0201] NFRR=(K W,1 / K W,2 ) / (K g,1 / K g,2 ) Formula (1)
[0202] The fracturing fluids prepared in Examples 17 to 25 after adjusting the pH were used to conduct water control experiments according to the above method, and the dimensionless fluid resistance ratio NFRR was calculated according to formula (1). The specific results are shown in Table 2.
[0203] Table 2. K in water control experiments W,1 , K W,2 , K g,1 , K g,2 and non-dimensional fluid resistance ratio (NFRR)
[0204]
[0205]
[0206] It can be seen in Table 2 that after the pH-adjusted fracturing fluids prepared in Examples 17 to 25 were injected into the core, the water phase permeability increased from K W,1From 4.8219 to 5.9273mD down to K W,2 From 1.2983 to 2.1627 mD, the water permeability decreased by 60% to 75%; the gas permeability increased from K g,1 From 19.1017 to 28.4622mD down to K g,2 The pH value of the fracturing fluid prepared in Examples 17 to 25 is 18.5743 to 26.3458 mD, and the gas permeability decreases by 2.7% to 7.8%; the water permeability decreases by a large margin, while the gas permeability decreases by a small margin, which proves that the fracturing fluid prepared in Examples 17 to 25 after adjusting the pH can achieve the effect of blocking water without blocking gas; furthermore, the dimensionless fluid resistance ratio (NFRR) represents the ratio of the flow resistance of different fluids. When the NFRR value is greater than 1, it means that the fracturing fluid has a greater effect on reducing the water permeability than the gas permeability. The larger the NFRR value, the greater the flow resistance of the water phase. The NFRR value of the fracturing fluid prepared in Examples 17 to 25 after adjusting the pH is 2.3465 to 3.7313, which proves that the fracturing fluid prepared in Examples 17 to 25 after adjusting the pH can significantly and selectively reduce the water permeability without affecting the performance of the gas permeability, and can meet the requirements of the water control fracturing technology for the fracturing fluid, and is applied to water control fracturing.
[0207] Although the present invention has been described with reference to specific embodiments, it will be appreciated by those skilled in the art that various changes may be made without departing from the true spirit and scope of the present invention. In addition, the subject matter, spirit and scope of the present invention may be varied to accommodate specific situations, materials, material combinations and methods. All of these changes are included within the scope of the claims of the present invention.
Claims
1. A composition comprising an organopolysiloxane, an emulsifier, a co-emulsifier and water.
2. The composition according to claim 1, characterized in that Taking the mass of the composition as 100%, the composition includes 10 wt % to 30 wt % of the organopolysiloxane, 20 wt % to 40 wt % of the emulsifier, 5 wt % to 15 wt % of the co-emulsifier, and the balance of water.
3. The composition according to claim 1 or 2, characterized in that The structural schematic diagram of the organopolysiloxane is shown in Formula I: Wherein, R is phenyl, C2 to C 12 One of an alkyl group and a trifluoropropyl group; a, b and c are the number of structural units; a, b, c are integers from 4 to 80, 1 to 10 and 2 to 20 respectively; The relative molecular mass of the organopolysiloxane is 700 to 10000; Preferably, in the formula I, R is phenyl; and / or The relative molecular mass of the organopolysiloxane is 700 to 8700; and / or a, b and c are integers from 10 to 60, 2 to 8 and 5 to 18 respectively; Preferably, a, b and c are integers of 20 to 60, 5 to 8 and 10 to 18 respectively.
4. The composition according to any one of claims 1 to 3, characterized in that The emulsifier is a mixture of a nonionic surfactant and an anionic surfactant; and / or The auxiliary emulsifier is an alcohol compound and / or an alcohol ether compound.
5. The composition according to claim 4, characterized in that The nonionic surfactant is a nonionic silicone surfactant and / or a sorbitan fatty acid ester; and / or The anionic surfactant is selected from at least one of alkylbenzene sulfonate, α-olefin sulfonate and alkyl sulfate; and / or The alcohol compound is at least one of n-propanol, isopropanol, n-butanol, isobutanol, ethylene glycol, propylene glycol and glycerol; and / or The alcohol ether compound is a C4 to C6 alcohol ether.
6. The composition according to claim 5, characterized in that The general structural formula of the nonionic silicone surfactant is shown in Formula II: Wherein, x, y and z are the number of structural units; x, y and z are integers from 1 to 10, 2 to 10 and 2 to 10, respectively; Preferably, in Formula II, x, y and z are integers of 1 to 6, 5 to 10 and 5 to 10 respectively.
7. The composition according to any one of claims 4 to 6, characterized in that In the emulsifier, the mass ratio of the nonionic surfactant to the anionic surfactant is 6:4 to 4:
6.
8. A fracturing fluid comprising a composition and water; The composition is the composition according to any one of claims 1 to 7.
9. The fracturing fluid according to claim 8, characterized in that: Taking the mass of the fracturing fluid as 100%, the fracturing fluid includes 0.2 wt % to 1.0 wt % of the composition and the balance being water.
10. Use of the composition according to any one of claims 1 to 7 or any one of the fracturing fluids according to claim 8 or 9 in water-controlled fracturing.
Citation Information
Patent Citations
Silicone polymer emulsions
CN101522758A
Comb-shaped modified polysiloxane anion water-base thick oil viscosity reducer and synthesizing method thereof
CN102516972A
Surfactant containing organic silicon group and used for decompression and augmented injection and preparation method and application thereof
CN113620984A
Micro-emulsion gas dispersing agent for gas well fracturing and preparation method of micro-emulsion gas dispersing agent
CN115558483A
